Propuesta de mejora en el proceso de deshidratación de rosas previo al tinturado en la empresa Jet Fresh Flower Growers, S.A. - Comina Fonseca, Edgar Mauricio (2022)
The present research was made in the Jet Fresh Flower Growers, S.A. enterprise, from Latacunga city, specifically in the improved roses area dehydration process, which is charged partially dehydrating the roses prior to the dyeing process (absorption), the process has an infrastructure, what it does not meet the necessary conditions to control the temperature variable, this makes that the process take more than 2 hours to complete. For this reason, the research work had as purpose to perform an experiment applying the temperature increase method, for searching the optimal temperature, what would reduce the dehydration time and increase production in the improved roses area. It was elaborated a dehydrating box with the process conditions, which it is analyzed into three different temperature ranges (24, 25 and 25°C) to increase the reliability. In the dehydrator box, it was placed 12 roses units with a 560 gr initial mass for a 1 hour and 20 minutes period, where it is got a final 500 gr mass, reducing 60 gr, what it can be identified as losing a 10,71% internal humidity of rose. The improvement proposal focuses its attention on the area, where it is made the roses dehydration process, that the area is completely closed, where there as no heat release, ensuring, what the roses number that enter the area to be same as those that can exit and thus, it speed up for the next absorption process.